2022
DOI: 10.1002/ptr.7551
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy and neuroinflammation pathways with plant‐derived natural compounds as potential antidepressant agents

Abstract: Major depressive disorder (MDD) is a life‐threatening disease that presents several characteristics. The pathogenesis of depression still remains poorly understood. Moreover, the mechanistic interactions of natural components in treating depression to target autophagy and neuroinflammation are yet to be evaluated. This study overviewed the effects of plant‐derived natural components in regulating critical pathways, particularly neuroinflammation and autophagy, associated with depression. A list of natural comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 229 publications
0
4
0
Order By: Relevance
“…In a systematic review by Moore et al, [78] RV was dose-dependently effective for the treatment of depression in animal models at doses between 10 and 80 mg/kg daily Our results indicated that RV, like FL, exhibited anxiolytic and antidepressant effects through control of the NF-B/NLRP3 axis similarly inhibition of NLRP3 by anti-inflammatory agents has been shown to alleviate mood disorders in animals. [79,80] Molecular studies showed that the RV administration attenuated the NF-κB/NLRP3 pathway through the regulation of NF-κB and NLRP3 inflammasome components (NLRP3, ASC, and proCaspase-1) in the HC. In line with our findings, RV treatment (40 or 80 mg/kg/day) could reverse behavioral changes animals induced by CUMS through regulating proinflammatory mediators (IL-6, IL-1β, & TNF-α) in the PFC and HC.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review by Moore et al, [78] RV was dose-dependently effective for the treatment of depression in animal models at doses between 10 and 80 mg/kg daily Our results indicated that RV, like FL, exhibited anxiolytic and antidepressant effects through control of the NF-B/NLRP3 axis similarly inhibition of NLRP3 by anti-inflammatory agents has been shown to alleviate mood disorders in animals. [79,80] Molecular studies showed that the RV administration attenuated the NF-κB/NLRP3 pathway through the regulation of NF-κB and NLRP3 inflammasome components (NLRP3, ASC, and proCaspase-1) in the HC. In line with our findings, RV treatment (40 or 80 mg/kg/day) could reverse behavioral changes animals induced by CUMS through regulating proinflammatory mediators (IL-6, IL-1β, & TNF-α) in the PFC and HC.…”
Section: Discussionmentioning
confidence: 99%
“…Certain constituents among these compounds demonstrate the ability to prevent the activation of NLRP3 inflammasomes. Compounds such as dihydroquercetin [ 76 ], resveratrol [ 77 ], quercetin [ 78 ], isoliquiritigenin [ 79 ], icariin [ 80 ], and oridonin [ 81 ] exhibit properties that suggest their suitability as promising candidates for regulating the activation of SARS-CoV-2-induced NLRP3 inflammasomes.…”
Section: Compounds Targeting Nlrp3 In the Treatment Of Sars-cov-2 Inf...mentioning
confidence: 99%
“…The activation of inflammasomes involves two distinct signaling pathways: Signal 1, known as the priming signal, and Signal 2, which corresponds to the activation signal, often referred to as the assembly step of the protein complex . The priming process is initiated by the activation of PRRs, such as NOD2 and Toll-like receptors (TLRs), by diverse stimuli.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%